Analysis of the Problems of Islamic Religious Education Teachers in Implementing the Independent Curriculum in Islamic Religious Education Learning - Siregar, Rahmayani; Siregar, Nurkholijah; Siregar, Nur Aisyah (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the problems faced by Islamic Religious Education (IRE) teachers in implementing the Independent Curriculum at Madrasah Tsanawiyah Zakiyun Najah, Sei Rampah District, Serdang Bedagai Regency. This research uses a qualitative approach with descriptive research type. Data collection techniques were carried out through interviews, observation, and documentation of the principal, deputy head of curriculum, IRE teachers, and several students. The results showed three main problems: teachers' difficulties in changing old mindsets and habits in learning, limited understanding and application of differentiated learning, and complexity in preparing teaching tools due to differences in curriculum between grade levels. Despite facing obstacles, teachers have made various efforts such as attending training, compiling teaching modules, and collaborating with colleagues. This study concludes that Independent Curriculum provides opportunities for more flexible and student-centered learning, but its success depends on teachers' readiness and continuous support. Therefore, intensive training and mentoring need to be carried out continuously to improve the quality of IRE learning implementation in accordance with the objectives of the Independent Curriculum.